1985
DOI: 10.1093/bja/57.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Resin Injection Studies of the Lumbar Extradural Space

Abstract: Two resin injection studies of the lumbar extradural space were performed to elucidate its size and shape. To counteract the lack of cerebrospinal fluid pressure in the cadaver, the subarachnoid space was filled with water. In group 1, the extradural injection of resin caused an immediate increase in subarachnoid pressure. The casts produced varied in thickness, but were situated predominantly in the dorsomedial and dorsolateral regions of the spinal canal. Thin anterior spread occurred in 40% of cases. In gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Cadaveric dissection [2] is subject to distortion because of postmortem autolysis and preservation with agents that alter tissue properties; furthermore, the loss of cerebrospinal fluid (CSF) pressure at death and possible increase in venous pressure result in changes in the relative volumes occupied by the dural sac and venous plexuses within the spinal canal. All techniques requiring the injection of fluid or air into the extradural region distort the anatomy; such methods have included resin injection studies [3], extradurography and computed tomography (CT) extradurography [4], extraduroscopy [5] and spinaloscopy [6]. More recently, a study using cryomicrotome sectioning of cadavers has provided some detailed information less distorted by artefact [7]-Magnetic resonance imaging (MRI) is the most rapidly advancing of the imaging specialties.…”
mentioning
confidence: 99%
“…Cadaveric dissection [2] is subject to distortion because of postmortem autolysis and preservation with agents that alter tissue properties; furthermore, the loss of cerebrospinal fluid (CSF) pressure at death and possible increase in venous pressure result in changes in the relative volumes occupied by the dural sac and venous plexuses within the spinal canal. All techniques requiring the injection of fluid or air into the extradural region distort the anatomy; such methods have included resin injection studies [3], extradurography and computed tomography (CT) extradurography [4], extraduroscopy [5] and spinaloscopy [6]. More recently, a study using cryomicrotome sectioning of cadavers has provided some detailed information less distorted by artefact [7]-Magnetic resonance imaging (MRI) is the most rapidly advancing of the imaging specialties.…”
mentioning
confidence: 99%
“…Resin injection studies of Harrison et al . (9) in autopsies of 20 cadavers found that flow of the resin formed a large posterior bulge with thin anterolateral projections on either side. Anterior spread was seen only in eight out of 20 cases as very thin and incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Savolaine et al . (10) described a central midline structure called plica mediana dorsalis with the dorsolateral ligaments issuing from it (9,16), of which four patterns have been described. Many cases of unilateral spread have been attributed to this (16,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study (8) demonstrated a sustained rise in intracranial pressure in response to epidural injections. Another study of resin injections in the cadaver (9) has shown an intracisternal rise in pressure with concomitent lumbar epidural space injection. Measurement of the fontanelle pressures in infants would probably reflect any rise in CSF pressures due to a cephalad displacement.…”
Section: Discussionmentioning
confidence: 99%